2013
DOI: 10.1111/j.1521-0391.2013.12024.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinician beliefs and attitudes about buprenorphine/naloxone diversion

Abstract: Background and Objectives Concern about diversion of buprenorphine/naloxone (B/N) in the U.S. may affect prescribing patterns and policy decisions. This study examines addiction treatment clinician beliefs and attitudes regarding B/N diversion. Methods Participants (n=369) completed a 34-item survey in 2010 during two national symposia on opioid dependence. We conducted multivariable regression, examining the relationship of perceived danger from B/N diversion with clinician characteristics and their beliefs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…Poor access to treatment could result in greater buprenorphine diversion, as could strong social and family networks, which are implicated in diversion of other opiate medications. 27 Alternatively, stigma and misunderstanding of MBT could result in greater concern about diversion …”
Section: Discussionmentioning
confidence: 99%
“…Poor access to treatment could result in greater buprenorphine diversion, as could strong social and family networks, which are implicated in diversion of other opiate medications. 27 Alternatively, stigma and misunderstanding of MBT could result in greater concern about diversion …”
Section: Discussionmentioning
confidence: 99%
“…If improving access to BMT also resulted in diversion to opioid naïve polysubstance users, there could be an overall negative public health impact; however, if concern about diversion resulted in stricter regulations, access to treatment could suffer, widening the treatment gap, and making it more difficult for marginalized PWUD to initiate BMT (Clark & Baxter, 2013). Additional data are necessary to estimate the prevalence of buprenorphine abuse; however, encouraging illicit buprenorphine users to initiate BMT instead of self-treating their addiction has clear advantages, such as education about risks, monitoring for other substance use, and treatment of co-morbid chronic conditions (Rowe, Jacapraro, & Rastegar, 2012; Schuman-Olivier et al, 2013). This requires access though, and even in a setting like New York City with numerous opioid treatment programs, capacity for treatment is only half of what is needed (McNeely et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Buprenorphine maintenance treatment (BMT), an option for opioid addiction treatment that has been available in the United States since 2002, is effective and may be more acceptable to patients than methadone maintenance, but it has failed to substantially reduce the treatment gap (Awgu, Magura, & Rosenblum, 2010; Mattick, Kimber, Breen, & Davoli, 2008). To date, most studies of barriers to BMT have examined the challenges of physicians or health systems to provide treatment (Korthuis et al, 2010; Roman, Abraham, & Knudsen, 2011; Savage et al, 2012; Schuman-Olivier et al, 2013), but many of the factors that prevent more people who use drugs (PWUD) from initiating BMT are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the US indicate an increasing risk of buprenorphine misuse and diversion [63]. A recent survey indicated that 40% of clinicians believe that the diversion of the buprenorphine-naloxone combination is a dangerous problem [64]. Buprenorphine was introduced to the US market in 2002 and is classified as a Schedule III medication [65]; it is the first-line option for office-based treatment [66,67].…”
Section: Extent Of the Problem In The Us And Non-european Countriesmentioning
confidence: 99%